The student experience of an open source Learning Management System - El Khalkhali, Imad (WCCAIS : 2014 World Congress on Computer Applications and Information Systems : Hammamet, Tunisia, 17-19 January, 2014, 2014)
According to the statistics of the Moroccan Ministry of Higher Education, more than 500,000 students are registered in our universities, so it's became impossible for them to work with traditional teaching methods. As a response to the increased number of students, many higher educational institutions have introduced and offered e-Learning systems as a tool to help the delivery of the course content and enhance the access of the courses and subjects by both students and teachers. This paper describes an experiment made at the National Business School of Tangier. This experience aims to investigate student's perceptions towards the usage of an e-learning platform through a survey which was conducted in semester 1 of session 2012/2013.